Structure formation in astrophysics - Chabrier, Gilles (Cambridge contemporary astrophysics., 2009)
Understanding the formation of objects at all scales in the universe, from galaxy clusters to stars and planets, is a major problem in modern astrophysics, and one of the most exciting challenges of twenty-first century astronomy. Even though they are characterized by different scales, the formation of planets, stars and galaxies share many common physical processes and are rooted in the same underlying domains of physics. This unique reference for graduate students and researchers in astrophysics was the first to cover structure formation on various scales in one volume. This book gathers together extensive reviews written by world experts in physics and astrophysics working in planet, star and galaxy formation, and related subjects. It addresses current issues in these fields and describes the recent observational status and theoretical and numerical methods aimed at understanding these problems.